2019
DOI: 10.1038/s41586-019-1789-8
|View full text |Cite
|
Sign up to set email alerts
|

Accretion of a giant planet onto a white dwarf star

Abstract: The detection of a dust disc around G29-38 1 and transits from debris orbiting WD 1145+017 2 confirmed that the photospheric trace metals found in many white dwarfs 3 arise from the accretion of tidally disrupted planetesimals 4 . The composition of these planetesimals is similar to that of rocky bodies in the inner solar system 5 . Gravitationally scattering planetesimals towards the white dwarf requires the presence of more massive bodies 6 , yet no planet has so far been detected at a white dwarf. Here we r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
172
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(175 citation statements)
references
References 101 publications
3
172
0
Order By: Relevance
“…In a subset of these systems, gaseous debris has also been observed that is co-orbital with the dust ). This gaseous material has so far been detected in seven systems (Gänsicke et al 2006(Gänsicke et al , 2007(Gänsicke et al , 2008Gänsicke 2011;Farihi et al 2012;Melis et al 2012;Wilson et al 2014), via the Dopplerbroadened, double-peaked line emission of the Ca 8600 Å triplet, which results from the Keplerian rotation of a flat disc (Horne & Marsh 1986) that is photoionised by the white dwarf Kinnear 2011;Gänsicke et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a subset of these systems, gaseous debris has also been observed that is co-orbital with the dust ). This gaseous material has so far been detected in seven systems (Gänsicke et al 2006(Gänsicke et al , 2007(Gänsicke et al , 2008Gänsicke 2011;Farihi et al 2012;Melis et al 2012;Wilson et al 2014), via the Dopplerbroadened, double-peaked line emission of the Ca 8600 Å triplet, which results from the Keplerian rotation of a flat disc (Horne & Marsh 1986) that is photoionised by the white dwarf Kinnear 2011;Gänsicke et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…No rocky material has been detected in this systemyet -although Gänsicke et al (2019) derived upper limits for abundances of rocky elements in the white dwarf's c 2020 RAS photosphere. The planet's location is uncertain, but was modelled to reside at a distance of about 0.07 au from the star.…”
Section: Introductionmentioning
confidence: 77%
“…However, in none of these systems with rocky pollution has a major planet been detected so far. Strikingly then, Gänsicke et al (2019) inferred the presence of a likely ice giant planet orbiting the volatile-rich white dwarf WD J091405.30+191412.25 (henceforth WD J0914+1914). This finding was based on the detection of abundant oxygen and sulfur (volatile elements) in combination with hydrogen throughout the system: both in the photosphere and the surrounding gaseous disc.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic emission lines suggest the existence of gaseous discs colocated with the compact circumstellar dust (Gänsicke et al 2006;Guo et al 2015). There is one exception to the compactness of gaseous discs, the disc around WD J0914+1914 is thought to be formed from an evaporating giant planet on a close-in orbit around the white dwarf (Gänsicke et al 2019).…”
Section: White Dwarf Systemsmentioning
confidence: 99%